Movement in world class tennis on clay and grass courts: a case study - Robinson, G.; O'Donoghue, P. (World Congress of Performance Analysis of Sport VIII, 2008)
The greater number of braking and acceleration from stationary events on clay is explained by players having more time to position themselves between shots on clay than on grass (O`Donoghue and Liddle, 1998; O`Donoghue and Ingram, 2001). However, with more time to play a shot on clay courts, the player can also force the opponent to move in a manner more likely to create a perturbation within the rally. One way of creating a perturbation and gain an advantage over the opponent is to"wrong-foot" the opponent forcing him to perform a disjointed turn to return to the corner of the court from where he had just moved from. These turns involved lunging movements which in addition to the longer rally durations on clay (O`Donoghue and Ingram, 2001) makes clay court tennis particularly challenging at the elite level of the game. There was no significant difference for the direction of movement before disjointed turns between clay and grass court performances (p > 0.05) or for the direction of movement after disjointed turns between clay and grass court play (p > 0.05). Therefore, the types of disjointed turn performed on the 2 surfaces are the same, but more of them are forced per rally on clay than on grass. There were many more sharp turns performed on grass than on clay and this was largely due to the greater number of times the player was able to attack the net on grass (O`Donoghue and Ingram, 2001). This involved changing path from moving across the baseline to travelling towards the net. In conclusion, the detailed analysis technique proposed by Robinson and O`Donoghue (2008) has allowed the movement within tennis rallies to be described in a much greater detail than before contributing to knowledge of the demands of men`s singles tennis at the elite level on clay and grass courts.